Incidence and disease course of new-onset diabetes mellitus in breast and colorectal cancer patients undergoing chemotherapy: A prospective multicenter cohort study. (April 2021) - Lee, Eun Kyung; Koo, Bokyung; Hwangbo, Yul; Lee, You Jin; Baek, Ji Yeon; Cha, Yong Jun; Kim, Sun Young; Sim, Sung Hoon; Lee, Keun Seok; Park, In Hae; Lee, Hyewon; Joo, Jungnam; et al.
Highlights: We investigated hyperglycemia that occurs during chemotherapy causing poor outcomes. New-onset diabetes mellitus incidence was 6.3% in cancer patients receiving chemotherapy with dexamethasone. Risk factors of new-onset diabetes mellitus were male and underlying impaired fasting glucose. After the end of chemotherapy, new-onset diabetes mellitus remitted in 64.7% patients. We found that remission was associated with higher C-peptide level at baseline. Abstract: Aims: To investigate the incidence of and risk factors for new-onset type 2 diabetes mellitus (DM) developed during chemotherapy that included steroids in cancer patients without DM. Methods: This multicenter, prospective, and observational cohort study enrolled 299 cancer patients without DM (aged > 18 years), planning 4–8 cycles of adjuvant chemotherapy. The endpoints were the incidence, remission rate, and independent determinants of new-onset DM during chemotherapy. Results: Between April 2015 and March 2018, 270 subjects with colorectal cancer or breast cancer (mean age, 51.0 years) completed the follow up (mean 39 months). Of whom, 17 subjects (6.3%) developed DM within a median time of 90 days (range, 17–359 days). Male sex (hazard ratio [HR], 15.839; 95% confidence interval [CI], 2.004–125.20) and impaired fasting glucose (IFG) at baseline (HR, 8.307; CI, 1.826–37.786) were independent risk factors. Six months after chemotherapy completion, 11/17 subjects (64.7%) experienced DM remission, associated with a significantly higher C-peptide level at baseline (C-peptide levels, 1.3 ng/mL in subjects with remission and 0.9 ng/mL in subjects without remission, age- and sex-adjusted P  = 0.007). Conclusions: DM incidence was 6.3% in patients who received chemotherapy with dexamethasone. Close monitoring for hyperglycemia is recommended, especially for men with IFG. Trial registration: ClinicalTrials.gov (NCT03062072).